English Speaking Anxiety Among The 10th Grade High School Students of SMKN 1 Klaten - Paquita Yovany Setiawan (Universitas Ahmad Dahlan, 2022)
Anxiety is an uncomfortable feeling, such as worry or fear which hamper a persons in doing something. Everyone has feelings of anxiety at some point in their life. English speaking anxiety usually happens because of lack of self-confidence and afraid of making mistake. The purpose of this study is to determine the causes of anxiety of the 10th graders when asked to speak English. This research will be conducted at SMKN 1 Klaten. Before starting a study of the causes of English speaking anxiety, the researcher starts by looking into anxiety levels and categorizing them into three categories: low, medium, and high. The data collection will be conducted through a questionnaire to be distrib